Effect of Cavity Cleanser With Long-Term Antibacterial and Anti-Proteolytic Activities on Resin–Dentin Bond Stability - Gou, Yaping; Jin, Wei; He, Yanning; Luo, Yu; Si, Ruirui; He, Yuan; Wang, Zhongchi; Li, Jing; Liu, Bin (Frontiers in Cellular and Infection Microbiology, 2021)
Objective: Secondary caries caused by oral microbiome dysbiosis and hybrid layers degradation are two important contributors to the poor resin-dentin bond durability. Cavity cleansers with long-term antimicrobial and anti-proteolytic activities are in demand for eliminating bacteria-induced secondary caries and preventing hybrid layers from degradation. The objectives of the present study were to examine long-term antimicrobial effect and anti-proteolytic potential of poly (amidoamine) dendrimers with amino terminal groups (PAMAM-NH2) cavity cleanser. Methods: Adsorption tests by ATR-IR and CLSM were first performed to evaluate whether the PAMAM-NH2 cavity cleanser had binding capacity to dentin surface to fulfill its relatively long-term antimicrobial and anti-proteolytic effects. For antibacterial testing, Streptococcus mutans, Actinomyces naeslundii and Enterococcus faecalis were grown on dentin surfaces, prior to the application of cavity cleanser. CFU counts and live/dead bacterial staining were performed to assess antibacterial effects. Gelatinolytic activity within the hybrid layers was directly detected by in-situ zymography. Adhesive permeability of bonded interface and microtensile bond strength were employed to assess whether the PAMAM-NH2 cavity cleanser adversely affected resin-dentin bonding. Finally, the cytotoxicity of PAMAM-NH2 was evaluated by the CKK-8 assay. Results: Adsorption tests demonstrated that binding capacity of PAMAM-NH2 on dentin surface was much stronger than that of 2% chlorhexidine (CHX) due to its binding was strong enough to resist PBS washing. Antibacterial testing indicated that PAMAM-NH2 significantly inhibited bacteria grown on the dentin disks compared with control group (p < 0.05), which was comparable with antibacterial activity of 2% CHX (p > 0.05). Hybrid layers condotioned with PAMAM-NH2 showed significant decrease in gelatin activity compared with control group. Furthermore, PAMAM-NH2 pretreatment did not adversely affect resin-dentin bonding because it did not decrease adhesive permeability and microtensile strength. CKK-8 assay showed that PAMAM-NH2 had low cytotoxicity on HDPCs and L929. Conclusions: PAMAM-NH2 cavity cleanser developed in this study could provide simultaneous long-term antimicrobial and anti-proteolytic activities for eliminating secondary caries that results from a dysbiosis in the oral microbiome and preventing hybrid layers from degradation due to its good binding capacity to dentin collagen matrix, which are crucial for the maintenance of resin-dentin bond durability.